Matéria orgânica em Planossolo Háplico sob sistemas de manejo no cultivo do arroz irrigado no Sul do Brasil - Rosa, Carla Machado da (2010)
In the south region from Rio Grande do Sul State, in,Brazil, 950 thousand hectares of soils are cultivated with rice, an important agricultural activity in that region, under an irrigation (flooded) system, using different soil management techniques. Studies regarding the organic matter (OM) dynamic in these soils are incipient, so this work aimed to evaluate the effect of irrigated rice management systems on the composition and quality of the OM from an Albaqualf, as well as, to investigate the OM stabilization mechanisms in this soil. Soil samples were collected in a long-term field experiment (21 years), from the 0-0,025, 0,025-0,05, 0,05-0,10 and 0,10-0,20 meters. The treatments evaluated are: ST traditional rice crop system: one year with rice crop under conventional tillage and two years of fallow; APC continuous rice crop system under conventional tillage and weeds control with herbicides; APD no-tillage system with rye-grass in the winter and rice in the summer; SN soil under natural conditions with native grassland. Soil samples were submitted to OM physical fractionation, and total organic carbon (TOC) and C contend in fractions were determinate by dry combustion analyzer, and carbon stocks adjusted according to the equivalent soil s mass. The chemical and molecular characteristics from this soil and OM fraction were determined by FTIR spectroscopy, RMN 13C (CP/MAS), and laser-induced fluorescence. No-tillage rice/rye-grass succession system was efficient in maintenance or increase SOM stocks until 0.05m deph. Particulate fraction increase demonstrates a higher maintenance level for carbon, showing the feasibility of this conservative system to contribute to the soil quality. Occluded light OM fraction was not susceptible to the effects of tillage systems used in irrigated rice crop, demonstrating a lower efficiency of the OM physical protection in soil aggregates. This situation may be related to the flooded condition affecting aggregates process. The OM spectroscopy characterization demonstrates for the flooded soil that functional groups are similar to the oxided soils. However, the portion of the CO-aquil structures from the free light and occluded light OM fraction were increased (from 39% to 52%), demonstrating a low level of OM decomposition in the deficient drainege environment. The OM from APC system were more humified than OM from APD and SN systems, mainly in the superficial levels, due to the loss of light OM fractions during the soil tillage.